ISG15 Promotes ERK1 ISGylation, CD8+ T Cell Activation and Suppresses Ovarian Cancer Progression - Yeung, Tsz-Lun (Cancers (Basel), 2018)
Increased number of tumor-infiltrating CD8+ lymphocytes is associated with improved survival in patients with advanced stage high grade serous ovarian cancer (HGSOC) but the underlying molecular mechanism has not been thoroughly explored. Using transcriptome profiling of microdissected HGSOC tissue with high and low CD8+ lymphocyte count and subsequent validation studies, we demonstrated that significantly increased ISG15 (Interferon-stimulated gene 15) expression in HGSOC was associated with high CD8+ lymphocyte count and with the improvement in median overall survival in both univariate and multivariate analyses. Further functional studies showed that endogenous and exogenous ISG15 suppressed ovarian cancer progression through ISGylation of ERK in HGSOC, and activation of NK cells and CD8+ T lymphocytes. These data suggest that the development of treatment strategies based on up-regulating ISG15 in ovarian cancer cells or increased circulating ISG15 in ovarian cancer patients is warranted.